Resilient marginal cities by encouraging intermodality strategies: Analysis of the Campanian marginal cities with criteria for intermodal business model - Di Ruocco, Irina (TeMA - Journal of Land Use, Mobility and Environment, 2022)
While metropolitan areas are evolving, funds and investments are investing in megacities, an overwhelming part of the population lives in peripheral and decentralized areas. Starting from an international view, the paper intends to offer a spatial cluster analysis on the main business models that can be reproduced in marginal areas. The literature points out that there is much study of inland areas but no spatial analysis of transportation for a particular band of areas, which includes marginal cities. A focus will be made on the marginal cities of Campania, starting from the strategies of internal areas. Encouraging intermodality with alternative and ICT-connected transport systems is a way to provide a mode of transport to cities in crisis. After an analysis of the territory, we will proceed with the identification of models of business for the decentralized areas of Campania. The main objective is to provide a set of criteria to identify the most suitable mobility services in main territorial contexts, from the point of view of population density, travel time from the nearest hub and use of ICT. This study should be seen as an initial approach to identifying strategies to develop the inland territories for first and last mile connection.